2011
DOI: 10.1007/s10802-011-9510-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exposure to Community Violence on Internalizing Symptoms: Does Desensitization to Violence Occur in African American Youth?

Abstract: The purpose of the current study was to examine the linear and curvilinear associations of exposure to community violence to internalizing symptoms in 251 African American adolescents (mean age = 12.86, SD = 1.28). Participants reported on exposure to community violence, anxiety symptoms, and depressive symptoms. Regression analyses were used to test the hypotheses and, consistent with predictions, the results indicated that the association between violence and depression was curvilinear; whereas the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
130
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(148 citation statements)
references
References 51 publications
12
130
2
4
Order By: Relevance
“…78 While direct and indirect exposures are not equivalent, the high level of relational, direct physical discipline toward a child may evoke some level of desensitization to other forms of violence resulting in a greater impact of direct violence with less additive effects with indirect. Such desensitization has been shown in Black youth exposed to community violence, 79 with a curvilinear relation between community violence exposures. In our current sample, we found no significant curvilinear or quadratic relation between indirect or direct violence and externalizing behavior; however, desensitization may also vary by behavioral conditions.…”
Section: Discussionmentioning
confidence: 79%
“…78 While direct and indirect exposures are not equivalent, the high level of relational, direct physical discipline toward a child may evoke some level of desensitization to other forms of violence resulting in a greater impact of direct violence with less additive effects with indirect. Such desensitization has been shown in Black youth exposed to community violence, 79 with a curvilinear relation between community violence exposures. In our current sample, we found no significant curvilinear or quadratic relation between indirect or direct violence and externalizing behavior; however, desensitization may also vary by behavioral conditions.…”
Section: Discussionmentioning
confidence: 79%
“…Fourth, adolescents who grow up surrounded by violence may become psychologically desensitized to its occurrence, 41 reducing both their perceived exposure to neighborhood violence and their likelihood of reporting mental health problems (however, there are conflicting findings 42 ). Lastly, exposure to neighborhood-level violence may be more strongly tied to delinquent and aggressive behaviors than to the depression/anxiety symptoms we could assess in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Some work suggests that exposure to community violence may affect depression and anxiety differently. One study showed that the relation between exposure to community violence and depression was curvilinear, whereas the relation between exposure to community violence and anxiety was linear (Gaylord-Harden et al 2011). Combining symptoms of depression and anxiety may have obscured interactive effects that operate differently in their prediction of symptoms of depression versus anxiety.…”
Section: J Youth Adolescencementioning
confidence: 99%
“…African American youth are especially susceptible to exposure to community violence. African American youth witness more violence than other youth and are more likely to be victims of assault and serious crime compared to other youth (Crouch et al 2000;Gaylord-Harden et al 2011;Sickmund and Puzzanchera 2014;Wilson et al 2012). Exposure to community violence during adolescence is a risk factor for internalizing (e.g., anxiety and depression) and externalizing problems (e.g., aggression and delinquency)-both of which pose serious risks for compromised functioning in adulthood (Brook et al 2013;Mason et al 2010;Yaroslavsky et al 2013).…”
Section: Introductionmentioning
confidence: 99%